Computational Antioxidant Capacity Simulation (CAOCS) Assay of Catechol, Resorcinol and Hydroquinone - Idowu, Sunday Olakunle; Adeyemo, Morenikeji Ayodele (Journal of Applied Solution Chemistry and Modeling, 2016)
There is an urgent need for a biorelevant antioxidant capacity assay, which is crucial to quality-assured polyphenol dietary supplements. We hypothesize that the 'position', more than the 'number' of phenolic groups, is critical to the antioxidant capacity of polyphenols. Computational Antioxidant Capacity Simulation (CAOCS) assay was implemented to test the hypothesis, while refinement of existing assay protocol was aimed at reducing the cost of analysis. The antioxidant capacities of resorcinol, catechol and hydroquinone (3 diphenol positional isomers) were determined by CAOCS assay. Photometric titration experiments and associated informatics that constitute CAOCS assay were evaluated through the use of small increments (< 1 mL) of antioxidant solution. Antioxidant capacity ranking of the positional isomers was found to be; hydroquinone > catechol > resorcinol, (60/g, 46/g and 28/g respectively). The relative bond strength of the phenolic groups, which governs the ranking, was accounted for by structural theory. Optimal 250 ÂµL increment of antioxidant solution afforded a 75% reduction of the amount of antioxidant required in the original assay protocol, where a 1 mL increment was used. CAOCS values vary widely for the positional isomers. The unique structure-antioxidant capacity-correlation (SACC) which confirmed our hypothesis is a signature of biorelevance. Significantly, microliter increments reduced the amount of active material required and hence, the cost of analysis. The methodology is thus attractive for profiling exotic and more expensive polyphenols. CAOCS assay holds a great promise of enabling quality-by-design (QbD) of polyphenol dietary supplements.